Fear of childbirth, anxiety and depression in three groups of primiparous pregnant women not attending, irregularly attending and regularly attending childbirth preparation classes - Robab Hassanzadeh; Fateme Abbas-Alizadeh; Shahla Meedya; Sakineh Mohammad-Al; Mojgan Mirghafourvand (BMC, 2020)
Abstract Background Lack of knowledge and fear of the unknown during pregnancy and childbirth make mothers fearful, worried, and anxious. Maternal fear and anxiety can lead to problems such as preterm childbirth and low birth weight. Increasing women's knowledge through prenatal education can prepare them for childbirth and improve their health. The present study was conducted to compare fear of childbirth, anxiety and depression during pregnancy in three groups of primiparous pregnant women who were either not attending, irregularly attending, or regularly attending childbirth preparation classes. Methods A total of 204 primiparous pregnant women attending health centers in Tabriz, Iran, were selected by cluster sampling and assigned to the following three groups: Not attending, irregularly attending (attending one to three sessions of classes) and regularly attending (attending four to eight sessions of classes). Childbirth fear, pregnancy anxiety and depression questionnaires were completed for them through interviews. The general linear model was used to compare their fear of childbirth and prenatal anxiety and depression. Results According to the general linear model, the scores of fear of childbirth (p <  0.001), anxiety (p <  0.001) and depression (p = 0.006) were significantly lower in the group of pregnant women regularly attending the classes compared to the non-attending group of women. No significant differences were observed between the regularly-attending and irregularly-attending groups in terms of fear of childbirth (p = 0.066), anxiety (p = 0.078), and depression (p = 0.128). Conclusion Prenatal training can reduce fear, anxiety and depression in primiparous women. Incorporating such training into prenatal care helps improve maternal health.